A Novel 3D Culture Model of Human ASCs Reduces Cell Death in Spheroid Cores and Maintains Inner Cell Proliferation Compared With a Nonadherent 3D Culture - Liang Luo (Frontiers Media S.A., 2021)
3D cell culture technologies have recently shown very valuable promise for applications in regenerative medicine, but the most common 3D culture methods for mesenchymal stem cells still have limitations for clinical application, mainly due to the slowdown of inner cell proliferation and increase in cell death rate. We previously developed a new 3D culture of adipose-derived mesenchymal stem cells (ASCs) based on its self-feeder layer, which solves the two issues of ASC 3D cell culture on ultra-low attachment (ULA) surface. In this study, we compared the 3D spheroids formed on the self-feeder layer (SLF-3D ASCs) with the spheroids formed by using ULA plates (ULA-3D ASCs). We discovered that the cells of SLF-3D spheroids still have a greater proliferation ability than ULA-3D ASCs, and the volume of these spheroids increases rather than shrinks, with more viable cells in 3D spheroids compared with the ULA-3D ASCs. Furthermore, it was discovered that the SLF-3D ASCs are likely to exhibit the abovementioned unique properties due to change in the expression level of ECM-related genes, like COL3A1, MMP3, HAS1, and FN1. These results indicate that the SLF-3D spheroid is a promising way forward for clinical application.